Firm Value and Its Predictors: An Examination of Companies Listed on Jakarta Islamic Index - Muhammad Fajrul Novrizal; Muhammad Arfan; Ratna Mulyany (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
This study aims to determine whether financial leverage, managerial ownership, profitability, company size, and the Islamic Social Reporting Index influence the firm value of companies listed on the Jakarta Islamic Index. The study population comprises companies listed on the Jakarta Islamic Index (JII) over the period of 2015-2019, with a total of 70 observations. This research period was chosen to avoid the potential effect of COVID-19 in the years after 2019. It is revealed that simultaneously all the financial leverage, managerial ownership, profitability, company size, and Islamic Social Reporting Index variables have a positive effect on firm value. Moreover, in the partial test, it was also found that each independent variable had a positive effect on firm value. The study implies and signifies the role of Islamic social reporting not only in ensuring the achievement of firms’ social accountability but also in increasing their value, particularly of those listed on the Islamic index.====================================================================================================ABSTRAK - Nilai Perusahaan dan Prediktornya: Pemeriksaan Perusahaan yang Terdaftar di Jakarta Islamic Index. Penelitian ini bertujuan untuk mengetahui apakah financial leverage, kepemilikan manajerial, profitabilitas, ukuran perusahaan, dan Islamic Social Reporting Index berpengaruh terhadap nilai perusahaan perusahaan yang terdaftar di Jakarta Islamic Index. Populasi penelitian adalah perusahaan yang terdaftar di Jakarta Islamic Index (JII) periode 2015-2019, dengan total 70 observasi. Periode penelitian ini dipilih untuk menghindari potensi efek COVID-19 di tahun-tahun setelah 2019. Terungkap bahwa secara simultan semua variabel financial leverage, kepemilikan manajerial, profitabilitas, ukuran perusahaan, dan Islamic Social Reporting Index berpengaruh positif terhadap perusahaan. nilai. Selain itu, pada uji parsial juga ditemukan bahwa masing-masing variabel independen berpengaruh positif terhadap nilai perusahaan. Studi ini menyiratkan dan menandakan peran pelaporan sosial Islam tidak hanya dalam memastikan pencapaian akuntabilitas sosial perusahaan, tetapi juga dalam meningkatkan nilainya, terutama yang terdaftar di indeks Islam.